Harmonisasi Standar Sertifikasi Halal Internasional dalam Perspektif Fikih Muamalah: Analisis Diplomasi Ekonomi Halal Indonesia di Pasar Global: Harmonizing International Halal Certification Standards: A Fiqh al-Muāmalāt Perspective on Indonesia’s Halal Economic Diplomacy in Global Markets - Kurnaemi Anita; Nasrullah bin Sapa (AL-KHIYAR: Jurnal Bidang Muamalah dan Ekonomi Islam, 2025)
The global halal industry is rapidly expanding as one of the strategic sectors in the international economy, with a continually growing market value that involves cross-border transactions, international organizations, and multilateral alliances. Although Indonesia occupies the position of one of the largest consumers of halal products in the world, its contribution as a major player in the global halal industry value chain still faces various structural and diplomatic challenges. This study aims to analyze the harmonization of international halal certification standards from the perspective of fiqh al-muʿāmalah and to formulate the role of Indonesia’s halal economic diplomacy in advocating for the protection of Muslim consumers in global markets. The research employs a qualitative-descriptive approach through library research and policy analysis. The findings indicate that, conceptually, most international halal certification standards converge with maqāṣid al-sharīʿah, particularly in the aspects of ṭahārah, ḥalāl al-dhabīḥah, and istibrā’. However, fragmented standards, divergent ijtihād on animal-derived enzymes and technical alcohol, and asymmetries among certifying authorities generate problems of traceability, the potential for monopolistic practices, and the risk of consumer harm, all of which contradict the legal maxim lā ḍarar wa lā ḍirār. This study underscores the importance of cross-madhhab collective ijtihād (ijtihād jamāʿī), the strengthening of an equitable mutual recognition scheme, and Indonesia’s proactive initiatives as a norm entrepreneur through halal economic diplomacy, including the proposal to establish an international Halal Dispute Board as a dispute settlement instrument and as a means of reinforcing the legitimacy of global halal standards grounded in fiqh al-muʿāmalah.